ANTIHYPERGLYCEMIC AND ANTINOCICEPTIVE ACTIVITY EVALUATION OF ‘KHOYER’ PREPARED FROM BOILING THE WOOD OF ACACIA CATECHU IN WATER - Rahmatullah, Mohammed; Hossain, Maraz; Mahmud, Arefin; Sultana, Nahida; Rahman, Sk. Mizanur; Islam, Md. Rashedul; Khatoon, Mujiba Salma; Jahan, Sharmin; Islam, Fatema (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
‘Khoyer’ is prepared by boiling the wood of Acacia catechu in water and then evaporating the resultant brew. The resultant hard material is powdered and chewed with betel leaves and lime with or without tobacco by a large number of the people of Bangladesh as an addictive psycho-stimulating and euphoria-inducing formulation. There are folk medicinal claims that khoyer helps in the relief of pain and is also useful to diabetic patients to maintain normal sugar levels. Thus far no scientific studies have evaluated the antihyperglycemic and antinociceptive effects of khoyer. The present study was carried out to evaluate the possible glucose tolerance efficacy of methanolic extracts of khoyer using glucose-induced hyperglycemic mice, and antinociceptive effects with acetic acid-induced gastric pain models in mice. In antihyperglycemic activity tests, the extract at different doses was administered one hour prior to glucose administration and blood glucose level was measured after two hours of glucose administration (p.o.) using glucose oxidase method. The statistical data indicated the significant oral hypoglycemic activity on glucose-loaded mice at all doses of the extracts tested. Maximum anti-hyperglycemic activity was shown at 400 mg extract per kg body weight, which was slightly less than that of a standard drug, glibenclamide (10 mg/kg body weight). In antinociceptive activity tests, the extract also demonstrated a dose-dependent significant reduction in the number of writhings induced in mice through intraperitoneal administration of acetic acid. Maximum antinociceptive activity was observed at a dose of 400 mg extract per kg body weight, which was greater than that of a standard antinociceptive drug, aspirin, when administered at a dose of 400 mg per kg body weight. The results validate the folk medicinal use of the plant for reduction of blood sugar in diabetic patients as well as the folk medicinal use for alleviation of pain.